POLA DAN MEKANISME PENGISIAN JABATAN HAKIM AGUNG PADA MAHKAMAH AGUNG REPUBLIK INDONESIA MENURUT SISTEM KETATANEGARAAN INDONESIA BERDASARKAN UUD 1945 - Fahmi Hafid Bachmid; Ahmad Yulianto Ihsan (UNIVERSITAS PAKUAN, 2022)
AbstrakSalah satu cara untuk menjamin independensi lembaga peradilan maupun hakim, UUD 1945 mengatur sedemikian rupa proses dan mekanisme pengisian jabatan hakim agung, yaitu dengan menyerahkan pengusulan calon hakim agung kepada suatu organ konstitusional yang independen yaitu KY yang dibentuk berdasarkan UUD 1945. Latar belakang pemberian kewenangan pengusulan calon hakim agung kepada KY, tidak terlepas dari pengalaman pengangkatan hakim agung sebelum perubahan UUD 1945 berdasarkan Undang-Undang Nomor 14 Tahun 1985 tentang Mahkamah Agung yang menentukan bahwa hakim agung diangkat oleh Presiden selaku Kepala Negara dari calon yang diusulkan oleh DPR yaitu diusulkan masing-masing dua calon untuk satu posisi hakim agung. Mekanisme tersebut dianggap tidak memberi jaminan independensi kepada hakim agung, karena penentuan hakim agung akan sangat ditentukan oleh Presiden dan usul DPR yang kedua-duanya adalah lembaga politik. Perubahan UUD 1945 dimaksudkan, antara lain, memberikan jaminan independensi yang lebih kuat kepada hakim agung, dengan menentukan mekanisme pengusulan hakim agung yang dilakukan oleh suatu lembaga negara yang independen pula, sehingga pengaruh politik dalam proses penentuan hakim agung dapat diminimalisasi. Dalam hal ini, UUD menghendaki adanya peran minimal kekuatan politik dari lembaga politik untuk menentukan hakim agung, agar hakim agung benar-benar independen. Keyword : Pola-Mekanisme Pengisian Jabatan, Hakim Agung, Mahkamah Agung AbstractOne way to guarantee the independence of the judiciary and judges, the 1945 Constitution regulates in such a way the process and mechanism for filling the position of Supreme Court justices, namely by submitting the nomination of candidates for Supreme Court justices to an independent constitutional organ, namely the Judicial Commission established under the 1945 Constitution. candidates for Supreme Court justices to KY, cannot be separated from the experience of appointing Supreme Court justices prior to the amendment to the 1945 Constitution based on Law Number 14 of 1985 concerning the Supreme Court which determines that Supreme Court Justices are appointed by the President as Head of State from the candidates proposed by the DPR, namely those proposed by each two candidates for one position of chief justice. This mechanism is considered not to guarantee the independence of the Supreme Court justices, because the determination of the Supreme Judges will be largely determined by the President and the proposal of the DPR, both of which are political institutions. The amendments to the 1945 Constitution are intended, among other things, to provide a stronger guarantee of independence to the Supreme Court justices, by determining the mechanism for proposing Supreme Court justices which is carried out by an independent state institution as well, so that political influence in the process of determining Supreme Court justices can be minimized. In this case, the Constitution requires a minimal role of political power from political institutions to determine Supreme Court justices, so that Supreme Court justices are truly independent. Keyword : Pattern-Mechanism of Position Filling, Supreme Court Justices, Supreme Court